Synthesis, Characterization and Antibacterial Activities of Some Mixed Ligand Complexes of Lanthanide(III) Ions - Rajendran, G.; Usha Devi, K.G. (Asian Journal of Chemistry, 2016)
Eight new complexes of lanthanide(III) ions with Schiff bases of p-anisidine as primary ligand and diphenyl sulphoxide as secondary ligand in the presence of any one of the three anions, viz., nitrate, perchlorate or thiocyanate were synthesized and characterized by infrared spectra, elemental analysis, molecular mass determination, thermal studies and electrical conductance measurements. All the complexes were screened for their antibacterial activities against S. aureus, E. coli, K. pneumoniae and Ps. aeruginosa. We have arrived at the composition of complexes by infrared spectral analysis, elemental analysis and conductance measurements as: (1) [Nd(HDDA)2(DPSO)(NO3)3]; (2) [Eu(HDDA)3(DPSO)(ClO4)2]ClO4; (3) [Gd(MDDA)3(DPSO)(NO3)3]; (4) [Pr(MDDA)4(DPSO)(ClO4)2]ClO4; (5) [Nd(DDA)4(DPSO)(NO3)3] (6) [Sm(DDA)4(DPSO)(NO3)3]; (7) [Sm(DDA)4(DPSO)(ClO4)3]; (8) [Nd(MNDA)4(DPSO)(NCS)3]